The organisational psychology of contract workers - Gan, Lynn (2009)
Contract workers are becoming increasingly prevalent within organisations. Prior research on contract workers has focused primarily on the determinants of employing contract workers, while relatively few studies have been done to compare the behaviour of the permanent employees and contract workers. This research investigated differences in the psychological behaviour of permanent employees and contract workers. It focused on the motivational and control differences between these two forms of employment structures. A sample of 196 respondents was drawn from two large organisations: a hospital and a multinational financial institution. The results were consistent with the theories of comparative institutions: permanent employees displayed higher levels of motivation than the contract workers in their work group. In addition, the supervisors indicated that they needed to control contract workers more than permanent employees, although workers themselves did not perceive any differences in terms of work autonomy.